Motion control of nonholonomic robots at low speed - Ľubica Miková; Alexander Gmiterko; Michal Kelemen; Ivan Virgala; Erik Prada; Darina Hroncová; Martin Varga (International Journal of Advanced Robotic Systems, 2020)
Many applications in robotics require precise tracking of the prescribed path. The aim of this article is to develop and verify by computer simulation a control design method which ensures that the “output” of the robot will move along a prescribed path. A virtual vehicle approach algorithm was used to track a predefined vehicle path. The idea behind this algorithm is that the movement of a virtual vehicle on a predefined path is controlled by a differential equation whose input is a control deviation representing the distance between a real and a virtual vehicle. The main advantage of the path-following approach is that, based on this approach, the feedback realized is invariant to the path.